Political Rhetoric as a Structural and Ideological Instrument in Star Wars and Harry Potter - Flotmann, Christina (Politics in Fantasy Media: Essays on Ideology and Gender in Fiction, Film, Television and Games)

(En-)Gendering a Popular Theatrical Genre. The Roles of Women in Nineteenth-Century British Melodrama - Tönnies, Merle

Anti-hegemoniale Strategien des Kleinen. Britische dokumentarische Farbfotografie als Kritik des Thatcherismus - Tönnies, Merle (Kulturen des Kleinen. Mikroformate in Literatur, Kunst und Medien)

Book review: Daniela Carpi (ed.) (2011). 'Bioethics and Biolaw through Literature.'Berlin: de Gruyter - Mildorf, Jarmila (Anglistik)

Exploring ‘our pitiful attempts at connection’: Dialogue in Corey Mesler’s Novel 'Talk' - Mildorf, Jarmila (). Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream)

Mapping Imaginary Dialogues in America - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream)

Figurenrede im Roman aus kognitionslinguistischer und narratologischer Perspektive am Beispiel von Jean Rhys’ Roman "Good Morning, Midnight" - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Imaginary Dialogues in American Literature and Philosophy: Beyond the Mainstream

Magic, Science, Technology and Literature

Advertising in American Culture - Janzen, Olga

Gesprochene Korpora des Englischen und ihre Anwendung in der Grammatikforschung - Mindt, Ilka (Grundlagen einer sprachwissenschaftlichen Quellenkunde)

The benefits of comics for language learning at the lower secondary level: A practical approach - Rumlich, Dominik (Teaching comics in the foreign language classroom)

Students’ general English proficiency prior to CLIL: Empirical evidence for substantial differences between prospective CLIL and non-CLIL students in Germany - Rumlich, Dominik (Content and language integrated learning (CLIL) in Europe)

Using comics in the classroom - The obvious way of creating a favourable learning environment? - Deane, Neil; Rumlich, Dominik (Medien und Interkulturalität im Fremdsprachenunterricht: Zwischen Autonomie, Kollaboration und Konstruktion)

Middeke,M. / Schnierer, P.P. / Sierz, A. (Hg.): The Methuen Guide to Contemporary British Playwrights - Tönnies, Merle (Anglia)

Rossow, H. Globalismus und Lew Labour - Tönnies, Merle (Anglistik. International Journal of English Studies)

Baumbach, S. / Neumann, B. / Nünning, A.: A History of British Drama - Tönnies, Merle (Anglistik. International Journal of English Studies)

"This Bright Inward Cinema of Thought" – Stream of Consciousness in Contemporary English Fiction - Strauß, Sara

‘Monstrous’ Homes: How Private Spaces Shape Characters’ Identities in 19th-century Sensation Fiction - Flotmann, Christina (Monstrous Geographies: Places and Spaces of the Monstrous)

Ambiguity in ‘Star Wars’ and ‘Harry Potter’: A (Post-)Structuralist Reading of Two Popular Myths - Flotmann, Christina

Populäre Mythen bei Star Wars und Harry Potter - Flotmann, Christina
Interview 2 Feb. 2013

Northern Landscapes and Anti-Thatcherite Positioning - Tönnies, Merle (Journal for the Study of British Cultures)

Feminising a Classical Male Plot Model? Black British Women Writers and the 'Bildungsroman' - Tönnies, Merle (International Journal of English Studies)

Book review: Christoph Schubert (2009). 'Raumkonstitution durch Sprache: Blickführung, Bildschemata und Kohäsion in Deskriptionssequenzen englischer Texte.' Tübingen: Max Niemeyer - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

Referential Frameworks and Focalization in a Craft Artist’s Life Story: A Socionarratological Perspective on Narrative Identity - Mildorf, Jarmila (Rethinking Narrative Identity: Persona and Perspective)

'Unnatural’ Narratives? The Case of Second-Person Narration - Mildorf, Jarmila (The Travelling Concepts of Narrative)

Teaching Medical Students about Medical Ethics and Domestic Violence: Alice Munro’s Short Story ‘Dimensions.’ - Mildorf, Jarmila (The Writing Cure: Literature and Medicine in Context)

The Writing Cure: Literature and Medicine in Context - Mildorf, Jarmila; Lembert-Heidenreich, Alexandra (The Writing Cure: Literature and Medicine in Context)

Studying Writing in Second Person: A Response to Joshua Parker - Mildorf, Jarmila (Connotations: Journal for Critical Debate)

Reading Fictional Dialogue: Reflections on a Cognitive-Pragmatic Reception Theory - Mildorf, Jarmila (Anglistik)

The Writing Cure: Literature and Medicine in Context

Perspectives on Mobility

Syntactic perspectives on directive speech acts : a contrastive study - Freudinger, Markus
This thesis is situated in the field of contrastive pragmatics and compares the syntactic realizations of equivalent directive speech acts in English and German. The term directive speech act is being used in a more narrow sense than intended by Searle (1975).Dramatic plays are used as data source for the original language and the translation into the other language. The four texts are Brechts “Mutter Courage und Ihre Kinder“, Dürrenmatts „Die Physiker“, Osbornes „Look Back in Anger“, and Leighs „Abigail‘s Party“.The central questions of this study are: Which forms are available in each language? Which specific function does a form fulfill in the system of each language? How do forms correspond across languages?In general, realizations as regular sentences, irregular sentences and non-sentences are possible. In the case of regular sentences, the subcategories imperative, declarative, yes-no interrogative, and wh-interrogative are possible in both languages. German also offers the adhortative and the infinitive. There are remarkable differences in terms of frequencies for these types.In general, German and English behave rather similar in their use of the clause types. The detailed qualitative description of specific examples constitutes the main part of the analysis and answers the following questions: which forms occur as equivalences? Under which conditions can declaratives and interrogatives be used directively?Non-sentences also play an important role. Formal categories, however, are not helpful; hence the utterances were grouped according to functional aspects. These are: propositional content, relationship between speaker and hearer, and illocutionary force.

Scientiﬁc Literature Retrieval based on Terminological Paraphrases using Predicate Argument Tuple - Choi, Sung-Pil; Song, Sa-kwang; Jung, Hanmin; Geierhos, Michaela; Myaeng, Sung Hyon (Information Science and Industrial Applications: Proceedings, International Conference, ISI 2012, Cebu, Philippines, May 2012)
The conceptual condensability of technical terms permits us to use them as effective queries to search scientific databases. However, authors often employ alternative expressions to represent the meanings of specific terms, in other words, Terminological Paraphrases (TPs) in the literature for certain reasons. In this paper, we propose an effective way to retrieve “de facto relevance documents” which only contain those TPs and cannot be searched by conventional models in an environment with only controlled vocabularies by adapting Predicate Argument Tuple (PAT). The experiment confirms that PAT-based document retrieval is an effective and promising method to search those kinds of documents and to improve terminology-based scientific information access models.

A Proof-of-Concept of D³ Record Mining using Domain-Dependent Data - Lee, Yeong Su; Geierhos, Michaela; Song, Sa-Kwang; Jung, Hanmin (Software Technology: Prooceedings, International Conference, SoftTech 2012, Cebu, Philippines, May 2012)
Our purpose is to perform data record extraction from onlineevent calendars exploiting sublanguage and domain characteristics. We therefore use so-called domain-dependent data (D³) completely based on language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Moreover, another important criteria is that our system is robust to DOM and layout modifications made by web designers. Thus, preliminary experimental results are provided to demonstrate proof-of-concept of such an approach tested on websites in the German opera domain. Furthermore, we could show that our proposed technique outperforms other data record mining applications run on event sites.

Customer Interaction Management goes Social: Getting Business Processes plugged in Social Networks - Geierhos, Michaela; Ebrahim, Mohamed (Computational Social Networks: Tools, Perspectives and Applications)
Within this chapter, we will describe a novel technical service dealing with the integration of social networking channels into existing business processes. Since many businesses are moving to online communities as a means of communicating directly with their customers, social media has to be explored as an additional communication channel between individuals and companies. While the English-speaking consumers on Facebook are more likely to respond to communication rather than to initiate communication with an organisation, some German companies already have regularly updated Facebook pages for customer service and support, e.g. Telekom. Therefore, the idea of classifying and evaluating public comments addressed to German companies is based on an existing demand. In order to maintain an active Facebook wall, the consumer posts have to be categorised and then automatically assigned to the corresponding business processes (e.g. the technical service, shipping, marketing, accounting, etc.). This service works like an issue tracking system sending e-mails to the corresponding person in charge of customer service and support. That way, business process management systems which are already used to e-mail communication can benefit from social media. This allows the company to follow general trends in customer opinions on the Internet; moreover it facilates the recording of two-sided communication for customer relationship management and the company’s response will be delivered through consumer’s preferred medium: Facebook.

Talking like a book. Investigating colloquialization as a change in written English - Mindt, Ilka (Oralité(s) et écriture(s))

Change in Contemporary English. A Grammatical Study - Mindt, Ilka; Leech, Geoffrey; Hundt, Marianne; Mair, Christian; Smith, Nicholas (Archiv für das Studium der neueren Sprachen und Literaturen 164: 249: 2)

Tagungsbericht: Symposium für Promovierende der Fremdsprachen in der Endphase – \textquotedblEndspurt für Dis(s)orientierte\textquotedbl - Armbrust, Laura; Rumlich, Dominik (Zeitschrift für Fremdsprachenforschung)

The effects of CLIL: Students’ linguistic accuracy in relation to internal and external learner variables - Rumlich, Dominik (Language learning and language use)

(Sprach-)Tests in der Praxis: Die Studie „Development Of North Rhine-Westphalian CLIL Students“ (DENOCS). - Rumlich, Dominik (Fremdsprachenunterricht empirisch erforschen. Grundlagen - Methoden - Anwendung)

Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices - Strauß, Sara (anglistik & englischunterricht)

Facets of Children’s Fears in Twentieth- and Twenty-First-Century Stream-of-Consciousness Fiction - Strauß, Sara (Who’s afraid of...? Facets of Fear in Anglophone Literature and Film)

Constructions of ‘Otherness’ in Frances Hodgson Burnett’s The Secret Garden - Strauß, Sara (A Hundred Years of The Secret Garden – Frances Hodgson Burnett’s Children’s Classic Revisited)

The Persistence of Modernism in Light (Critical Engagements: A Journal of Criticism and Theory: Special Section: Eva Figes)

Der Zauber Magischer Welten - Flotmann, Christina
Interview 11 Oct. 2012

Spatial Representations of British Identities

A Bricolage of Identities in Crisis. Colour Photography Documenting Northern England under Thatcher - Tönnies, Merle (Facteurs d'Identité / Faktoren der Identität)

Polite Conversation, Implicatures, and Comical Effect: Jonathan Swift and P. G. Wodehouse - Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

New Perspectives on Imaginary Dialogues: An Interdisciplinary Dialogue - Kinzel, Till; Mildorf, Jarmila (Imaginary Dialogues in English: Explorations of a Literary Form)

Second-Person Narration in Literary and Conversational Storytelling - Mildorf, Jarmila (Storyworlds)

Imaginary Dialogues in English: Explorations of a Literary Form

Mobility in Literature and Culture, 1500-1900

A Social Media Customer Service - Geierhos, Michaela; Lee, Yeong Su; Schuster, Jörg; Kobothanassi, Despina; Bargel, Matthias (Proceedings of the 22nd ACM Conference on Hypertext and Hypermedia)

SCM - A Simple, Modular and Flexible Customer Interaction Management System - Schuster, Jörg; Lee, Yeong Su; Kobothanassi, Despina; Bargel, Matthias; Geierhos, Michaela (International Conference on Information Society (i-Society 2011))
SCM is a simple, modular and flexible system for web monitoring and customer interaction management. In our view, its main advantages are the following: It is completely web based. It combines all technologies, data, software agents and human agents involved in the monitoring and customer interaction process. It can be used for messages written in any natural language. Although the prototype of SCM is designed for classifying and processing messages about mobile-phone related problems in social networks, SCM can easily be adapted to other text types such as discussion board posts, blogs or emails. Unlike comparable systems, SCM uses linguistic technologies to classify messages and recognize paraphrases of product names. For two reasons, product name paraphrasing plays a major role in SCM: First, product names typically have many, sometimes hundreds or thousands of intralingual paraphrases. Secondly, product names have interlingual paraphrases: The same products are often called or spelt differently in different countries and/or languages. By mapping product name variants to an international canonical form, SCM allows for answering questions like Which statements are made about this mobile phone in which languages/in which social networks/in which countries/...? The SCM product name paraphrasing engine is designed in such a way that standard variants are assigned automatically, regular variants are assigned semiautomatically and idiosyncratic variants can be added manually. With this and similar features we try to realize our philosophy of simplicity, modularity and flexibility: Whatever can be done automatically is done automatically. But manual intervention is always possible and easy and it does not conflict in any way with the automatic functions of SCM.
Keywords: Social Media Business Integration; Contact Center Application Support; Monitoring Social Conversations; Social Customer Interaction Management; Monitoring; Software Agents

Buy, Sell, or Hold? Information Extraction from Stock Analyst Reports - Lee, Yeong Su; Geierhos, Michaela (Modeling and Using Context: 7th International and Interdisciplinary Conference, CONTEXT 2011, Karlsruhe, Germany, September 26-30, 2011, Proceedings)
This paper presents a novel linguistic information extraction approach exploiting analysts’ stock ratings for statistical decision making. Over a period of one year, we gathered German stock analyst reports in order to determine market trends. Our goal is to provide business statistics over time to illustrate market trends for a user-selected company. We therefore recognize named entities within the very short stock analyst reports such as organization names (e.g. BASF, BMW, Ericsson), analyst houses (e.g. Gartner, Citigroup, Goldman Sachs), ratings (e.g. buy, sell, hold, underperform, recommended list) and price estimations by using lexicalized finite-state graphs, so-called local grammars. Then, company names and their acronyms respectively have to be cross-checked against data the analysts provide. Finally, all extracted values are compared and presented into charts with different views depending on the evaluation criteria (e.g. by time line). Thanks to this approach it will be easier and even more comfortable in the future to pay attention to analysts’ buy/sell signals without reading all their reports.

Processing Multilingual Customer Contacts via Social Media - Geierhos, Michaela; Lee, Yeong Su; Bargel, Matthias (Multilingual Resources, Multilingual Applications: Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we will describe a new approach to customer interaction management by integrating social networking channels into existing business processes. Until now, contact center agents still read these messages and forward them to the persons in charge of customer’s in the company. But with the introduction of Web 2.0 and social networking clients are more likely to communicate with the companies via Facebook and Twitter instead of filling data in contact forms or sending e-mail requests. In order to maintain an active communication with international clients via social media, the multilingual consumer contacts have to be categorized and then automatically assigned to the corresponding business processes (e.g. technicalservice, shipping, marketing, and accounting). This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer relationship management.
Keywords: Classification of Multilingual Customer Contacts; Contact Center Application Support; Social Media Business Integration

Towards Multilingual Biographical Event Extraction - Geierhos, Michaela; Bouraoui, Jean-Leon; Watrin, Patrick (Multilingual Resources, Multilingual Applications. Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we describe the special requirements of a semantic annotation scheme used for biographical event extraction in the framework of the Europeancollaborative research project Biographe. This annotationscheme supports interlingual search for people due to its multilingual support covering four languages such as English, German, French and Dutch.
Keywords: Biographical Event Extraction for Interlingual People Search; Semantic Annotation Scheme

Customer Interaction 2.0: Adopting Social Media as Customer Service Channel - Geierhos, Michaela (Journal of Advances in Information Technology)
Since customers first share their problems with a social networking community before directly addressing a company, social networking sites such as Facebook, Twitter, MySpace or Foursquare will be the interface between customer and company. For this reason, it is assumed that social networks will evolve into a common communication channel – not only between individuals but also between customers and companies. However, social networking has not yet been integrated into customer interaction management (CIM) tools. In general, a CIM application is used by the agents in a contact centre while communicating with the customers. Such systems handle communication across multiple different channels, such as e-mail, telephone, Instant Messaging, letter etc. What we do now is to integrate social networking into CIM applications by adding another communication channel. This allows the company to follow general trends in customer opinions on the Internet, but also record two-sided communication for customer service management and the company’s response will be delivered through the customer’s preferred social networking site.
Keywords: Social Media Business Integration; Multichannel Customer Interaction Management; Contact Centre Application Support

Adjective complementation by that-clauses: An empirical study - Mindt, Ilka

Corpus Linguistics and the Description of English - Mindt, Ilka; Lindquist, Hans (ICAME Journal 35)

Anglistische Korpuslinguistik. Eine Einführung. Grundlagen der Anglistik und Amerikanistik 33 - Mindt, Ilka; Mukherjee, Joybrato (Anglistik. International Journal of English Studies, 22, 1)

Introducing Narrative in Drama - Flotmann, Christina; Tönnies, Merle (Narrative in Drama: CDE Studies 18)

Narrative in Drama

Narrative in Drama

Book review: Arthur W. Frank (2010). 'Letting Stories Breathe: A Socio-Narratology.' Chicago: University of Chicago Press - Mildorf, Jarmila (Biography)

BiographIE - Biographical Information Extraction from Business News - Geierhos, Michaela; Blanc, Olivier (Actes du 27e Colloque international sur le lexique et la grammaire (L’Aquila, 10-13 septembre 2008))

BiographIE - Klassifikation und Extraktion karrierespezifischer Informationen - Geierhos, Michaela
Das wesentliche Ziel der vorliegenden Publikation ist die Erstellung von sprachspezifischen Modulen im Bereich der Biographischen InformationsExtraktion (BiographIE). Unter Informationsextraktion verstehen wir die automatisierte Analyse von Dokumenten im Hinblick auf das Entdecken und Normalisieren von semantisch interessanten Entitäten und deren Eigenschaften. Das Hauptgewicht der Arbeit liegt auf sehr detaillierten und umfangreichen linguistischen Grammatiken im Bereich der Beschreibung von Personen und deren Beziehungen zu anderen relevanten Entitäten (z.B. Organisationen, Orte, Datums- und Zeitangaben) in Texten. Neben den öffentlichen und privaten Eigenschaften von Personen (Geburtsdatum, Nationalität etc.) sollen vor allem alle biographisch relevanten Attribute aus Texten extrahiert werden können. Dazu gehören in erster Linie berufliche Werdegänge, Anstellungsverhältnisse, Rollen in Firmen und ähnliche Eigenschaften. Da alle diese Attribute in unzählbar verschiedenen Formen ausgedrückt werden können, müssen sehr umfangreiche Lexika und sehr detaillierte grammatische Beschreibungen erstellt werden. Dies geschieht hauptsächlich bei der systematischen Evaluierung von Korpora. Je umfangreicher diese sind, desto adäquater werden die erstellten Grammatiken sein. Im Gegensatz zu den heute üblichen statistischen, auf maschinellem Lernen basierenden Verfahren setzen wir auch umfangreiche semi-automatisch erstellte, linguistische Module ein, die dann durch systematische Evaluierung auf Korpora schnell ergänzt und verbessert werden können. Basierend auf unseren Extraktionsmethoden ist es nun möglich, im Bereich der semantischen Suche deutliche Fortschritte zu machen. Insbesondere Personensuchmaschinen können sich unsere detaillierten Analysemethoden zu Nutze machen, um beispielsweise zu ermitteln, wer in welcher Funktion bei welcher Firma von wann bis wann beschäftigt war.
Keywords: Natural Language Processing

Beiträge der Sektion I "'Spoken' English through the Centuries." Sprachwissenschaftliche Sektion beim Anglistentag 2009 in Klagenfurt. - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Spoken English through the centuries: Introduction - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Methoden der Korpuslinguistik: Der korpus-basierte und der korpus-geleitete Ansatz - Mindt, Ilka (Kompendium Korpuslinguistik. Eine Bestandsaufnahme aus deutsch-tschechischer Perspektive)

Reading British Spaces

Das englische Drama der Gegenwart: Kategorien-Entwicklungen-Modellnterpretationen

The Features of Meanings of Orality in Black British Performance Poetry - Tönnies, Merle; Sand, Andrea (Anglistentag 2009 Klagenfurt. Proceedings)

Transgressive Melodrama. The 'Sensational' 1860s and their After-Effects - Tönnies, Merle (Victorian Highways - Victorian Byways. New Approaches to Nineteenth-Century British Literature and Culture)

Negotiating Deviance: Identity, Trajectories and Norms in a Graffitist’s Interview Narrative - Mildorf, Jarmila (Telling Stories: Language, Narrative, and Social Life)

Book review: Franz K. Stanzel. Telegonie -- Fernzeugung: Macht und Magie der Imagination. Wien: Böhlau - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Narratology and the Social Sciences - Mildorf, Jarmila (Postclassical Narratology: Approaches and Analyses)

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Assmann, A.: Einführung in die Kulturwissenschaft - Tönnies, Merle (Anglistik. International Journal of English Studies)

Lionel Johnson - Flotmann, Christina (Kindlers Literaturlexikon)

Shelagh Delaney 'A Taste of Honey' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'A Map of the World' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Knuckle' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Plenty' - Tönnies, Merle (Kindlers Literaturlexikon)

Ann Patricia Jellicoe 'The Knack' - Tönnies, Merle (Kindlers Literaturlexikon)

Stephen Poliakoff 'Strawberry Fields' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Amadeus' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Equus' - Tönnies, Merle (Kindlers Literaturlexikon)

George Bernard Shaw 'Mrs Warren's Profession' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Mrs Henry Wood' - Tönnies, Merle (Kindlers Literaturlexikon)

Mary Elisabeth Braddon 'Lady Audley's Secret' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Lady Windermere's Fan' - Tönnies, Merle (Kindlers Literaturlexikon)

Alan Ayckbourn 'Woman in Mind' - Tönnies, Merle (Kindlers Literaturlexikon)

Wilkie Collins 'The Moonstone' - Tönnies, Merle (Kindlers Literaturlexikon)